Using near-infrared reflectance spectroscopy (NIRS) to assess distal-limb perfusion on venoarterial (V-A) extracorporeal membrane oxygenation (ECMO) patients with femoral cannulation. (November 2018) - Patton-Rivera, Killian; Beck, James; Fung, Kenmond; Chan, Christine; Beck, Matthew; Takayama, Hiroo; Takeda, Koji
Background: Patients requiring V-A ECMO who receive femoral cannulation have an associated risk of distal, lower-limb hypoperfusion and ischemia of the cannulated leg. This pilot study evaluated the usefulness of non-invasive lower-limb oximetry, using near-infrared reflectance spectroscopy (NIRS) to detect limb ischemia. Methods: Between June 2016 and January 2017, 25 patients receiving femoral V-A ECMO were continuously monitored using the CASMED Fore-Sight Elite (CAS Medical Systems Inc., Branford, CT) tissue oximeter. A retrospective pilot study was conducted to review the correlation between NIRS tissue saturations (StO2 ) and clinical indications of limb ischemia. Patients were monitored for StO2 s less than 50% for more than four minutes or StO2 differentials between the cannulated and non-cannulated legs greater than 15%. Results: Twenty-five patients (age 22-78) were monitored with NIRS. Six patients had clinical indications of lower-limb ischemia: cold limb, mottled skin and pulseless Doppler ultrasound. All six patients had StO2 s below 50% that persisted for longer than four minutes. Of the 25 patients, one patient had a false-positive indication of hypoperfusion with StO2 below 50% for more than four minutes due to a venous saturation below 30%. Another patient had a false-positive pulseless Doppler ultrasound caused by high doses of pressor support. The StO2 was greater than 60%, which confirmed the clinical determination of adequate perfusion. Five patients had StO2 s below 50% for less than four minutes and none of these patients had clinical indications of lower-limb hypoperfusion. All patients with cannula-related obstruction of flow to the distal portion of the leg had StO2 differentials greater than 15%. No patients without cannula-related obstruction to flow had StO2 differentials greater than 15%. Conclusion: Advancements in NIRS technology seem to have improved its accuracy for continuous, non-invasive monitoring of regional tissue and may provide clinicians with an additional metric to protect the distal portion of the cannulated leg.